A medium-sized, open-economy, fiscal DSGE model of South Africa - Johannes Hermanus Kemp; Hylton Hollander (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Much of the research on fiscal multipliers has used reduced form modelling approaches. While these models have been extended to include richer controls and identification approaches, it remains unclear whether shocks identified capture the true structural shocks. An alternative way to identify these shocks is through dynamic stochastic general equilibrium models. This paper estimates an open-economy dynamic stochastic general equilibrium model for South Africa, but with a more detailed fiscal block, to measure the impact of fiscal policy shocks on macroeconomic outcomes. Simulations indicate that government spending and investment multipliers are generally positive, albeit smaller than 1. Second, it is found that taxes are highly distortionary, with large negative multipliers for private consumption and investment. In contrast, the impact of tax shocks on output is ambiguous. Finally, simulations suggest that government consumption spending and labour and consumption taxes are the most effective instruments for stabilizing debt after a fiscal shock.
Keywords: C32; E32; E62; H62; H63; 330; dynamic stochastic general equilibrium model; fiscal policy; fiscal multiplier; Bayesian inference